Answer:
changing the polarity or direction of the battery changes the sign of the voltage and the current
Explanation:
The sign of current and voltage are due to established conventions.
The way that a DC circuit with negative current values is by changing the polarity of the power source or by inverting the battery, this creates that the electrons move in the opposite direction
Changing the battery also changes the direction of the power difference, since the potential from positive to negative, in most cases negative is assigned a potential of zero volts
In summary, changing the polarity or direction of the battery changes the sign of the voltage and the current
Answer:
Remain the same
Explanation:
There is no relationship between amplitude frequency.
Given
Weight of the block A, Wa = 20 lb, weight of block B Wb = 50 lb. Applied
force to block A, P = 6lb, coefficient of static friction µs = 0.4, coefficient
of kinetic friction µk = 0.3. If a force P
is applied to the body, no relative motion will take place until the applied
force is equal to the force of friction Ff, which is acting opposite to the
direction of motion. Magnitude of static force of friction between block A and
block B, Fs = µsN, where N is
reaction force acting on block A. Now, resolve the forces Fx = max. P = (mA +
mB)a,
6 = (20 / 32.2 + 50 / 32.2)a
2.173a = 6
A = 2.76 ft/s^2
To check slipping occurs between block A and block B, consider block A:
P – Ff = mAaA
6 – Ff = 1.71
Ff = 4.29 lb
And also,
N = wA. We know static friction,
Fs = µsN
Fs = 0.4 x 20
Fs = 8lb
Frictional force is less than static friction. Ff < Fs
<span>Therefors, acceleration of block A, aA = 2.76 ft/s^2, acceleration of
block B aB = 2.76 ft/s^2</span>
Answer:
(a) k = 30.33 N/m
(b) a = 9.8 m/s²
Explanation:
First, we need to find the force acting on the bungee jumper. Since, this is a free fall motion. Therefore, the force must be equal to the weight of jumper:
F = W = mg
F = (65 kg)(9.8 m/s²)
F = 637 N
(a)
Now applying Hooke's Law:
F = k Δx
where,
k = spring constant = ?
Δx = change in length of bungee cord = 33 m - 12 m = 21 m
Therefore,
637 N = k(21 m)
k = 637 N/21 m
<u>k = 30.33 N/m</u>
<u></u>
(b)
Since, this is free fall motion. Thus, the maximum acceleration will be the acceleration due to gravity.
a = g
<u>a = 9.8 m/s²</u>